Ambush Marketing: Creativity vs. Controversy - Nufer, Gerd (American Journal of Management, 2025)
Ambush marketing, a tactic non-sponsors use to associate with major sporting events, raises ethical, legal, and strategic questions. This paper explores the phenomenon from historical, theoretical, and practical perspectives, highlighting its dual nature as a creative marketing tool and a controversial threat to official sponsorships. Drawing on case studies, it categorizes ambush marketing strategies into direct, indirect, and destructive forms, examining their effectiveness and consequences. While ambush marketing enables brands to leverage the visibility of events without official sponsorship costs, it challenges the exclusivity and financial stability of event organizers and sponsors. The discussion considers legal frameworks, consumer perceptions, and the broader impact on sports sponsorship markets. Ultimately, the analysis suggests a balanced approach to regulation, acknowledging ambush marketing’s potential to drive innovation while emphasizing the need for fair competition and protection of sponsorship rights. This paper contributes to a nuanced understanding of ambush marketing’s implications in the evolving landscape of sports marketing.